Hepatic Small Ubiquitin‐Related Modifier (SUMO)–Specific Protease 2 Controls Systemic Metabolism Through SUMOylation‐Dependent Regulation of Liver–Adipose Tissue Crosstalk - Liu, Yang; Dou, Xin; Zhou, Wei‐yu; Ding, Meng; Liu, Ling; Du, Ruo‐qi; Guo, Liang; Qian, Shu‐wen; Tang, Yan; Yang, Qi‐qi; Pan, Dong‐ning; Li, Xiao‐ying; et al. (Hepatology (Baltimore, Md.), 2021)
Background and Aims NAFLD, characterized by aberrant triglyceride accumulation in liver, affects the metabolic remodeling of hepatic and nonhepatic tissues by secreting altered hepatokines. Small ubiquitin‐related modifier (SUMO)–specific protease 2 (SENP2) is responsible for de‐SUMOylation of target protein, with broad effects on cell growth, signal transduction, and developmental processes. However, the role of SENP2 in hepatic metabolism remains unclear. Approach and Results We found that SENP2 was the most dramatically increased SENP in the fatty liver and that its level was modulated by fed/fasted conditions. To define the role of hepatic SENP2 in metabolic regulation, we generated liver‐specific SENP2 knockout (Senp2‐LKO) mice. Senp2‐LKO mice exhibited resistance to high‐fat diet–induced hepatic steatosis and obesity. RNA‐sequencing analysis showed that Senp2 deficiency up‐regulated genes involved in fatty acid oxidation and down‐regulated genes in lipogenesis in the liver. Additionally, ablation of hepatic SENP2 activated thermogenesis of adipose tissues. Improved energy homeostasis of both the liver and adipose tissues by SENP2 disruption prompted us to detect the hepatokines, with FGF21 identified as a key factor markedly elevated in Senp2‐LKO mice that maintained metabolic homeostasis. Loss of FGF21 obviously reversed the positive effects of SENP2 deficiency on metabolism. Mechanistically, by screening transcriptional factors of FGF21, peroxisome proliferator–activated receptor alpha (PPARα) was defined as the mediator for SENP2 and FGF21. SENP2 interacted with PPARα and deSUMOylated it, thereby promoting ubiquitylation and subsequent degradation of PPARα, which in turn inhibited FGF21 expression and fatty acid oxidation. Consistently, SENP2 overexpression in liver facilitated development of metabolic disorders. Conclusions Our finding demonstrated a key role of hepatic SENP2 in governing metabolic balance by regulating liver–adipose tissue crosstalk, linking the SUMOylation process to metabolic regulation.